Analysis and simulation of the reverse recovery mechanism of a PIN diode - Zhao, Qian (Nanyang Technological University, 2023)
The reverse recovery characteristics of the diode are very important in the power electronic field, so it needs to be further researched. In this dissertation, PIN diode reverse recovery mechanism is first analyzed in detail, then the PIN diode shutoff physical process is thoroughly investigated. The establishment of a PIN diode reverse recovery process step calculation model is deduced. Some simplified approximations are based on the reverse recovery time calculation formulas. We analyzetwo conditions for PIN diode soft recovery. One isincreasing the minority carrier lifetime inthebaseregion,whichcanincreasethereverserecoverytimeandthesoftnessfactor. The other is decreasing the carrier concentration in the base region, which can reduce thereversecurrentpeak. Reasonablyloweringthebasezonewidthandminoritycarrier life can reduce the reverse recovery time. Then using Silvaco, we can establish the analysis of the PIN diode reverse recovery process of the device structure model and simulation circuit. We also analyze the process in each stage of intrinsic area carrier distribution and verify the simplified approximation of the time calculation formula. By simulating theimportant factors,we canseehowthesefactors influence thereverse recovery peak current and time. The conclusion lays the foundation for the reasonable design of the related parameters of the PIN diode.